Promoting culture and spirituality in an audiovisual society: Pope Saint John Paul II's teachings on cinema. Issue 2 (3rd July 2021) - Pardo, Alejandro
Abstract: During his pontificate (1978‒2005), John Paul II always approached cinema in a positive way, different from the reluctance that, generally speaking and with nuances, the Catholic Church initially manifested towards it. Aware of the powerful influence the film medium has as agent of socialization and culturalization, John Paul II poses the ethical challenge of using film's great potential to promote man and society. Analysing extensively Pope Wojtyła's statements on cinema, this article identifies and systematically presents their main ethical ideas. John Paul II expresses a positive vision of the cinematographic medium. His teaching combines respect and admiration with critical analysis, trust with warnings, the defense of freedom with the call to social responsibility for film industry professionals as well as for viewers. The results of this first systematic research on John Paul II's magisterium may open the way to future studies on the relationship between cinema and society, also on the links between the transcendentals of being (beauty, truth, goodness) and the artistic, socio-cultural and industrial approaches to cinema.